Síntese da zeólita Beta usando planejamento experimental e emprego na isomerização do n-hexano - Oliveira, Kátia Dionísio de (2012)
This work aimed to apply the Design Of Experiment (DOE) methodology as an auxiliary tool to evaluate the conditions of synthesis of the aluminum-rich zeolite Beta. Bimetallic catalysts with 50% platinum and 50% nickel (50Pt50Ni) supported on zeolites with various Si/Al ratios were synthesized, characterized and evaluated in the isomerization of n-hexane. In the first part of this work, five variables related to the synthesis of zeolite Beta were evaluated by a series of statistical designs, in which the response variables were the relative intensities of the X-ray patterns and the yield of phase BEA. The results of the t-test showed that the ratio TEAOH/SiO2 is not significant for the formation and crystallization of zeolite Beta. However, the interaction of this variable with the Si/Al ratio was statistically significant. In order to obtain the aluminum-rich zeolite Beta, the samples were synthesized with partial substitution of cations TEA+ by cations Na+. The XRD patterns of these samples showed that BEA phase was formed using a Si/Al ratio of 5,0 and 7.5. These low values of Si/Al ratio were confirmed by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and energy-dispersive X-ray spectroscopy (EDS). Information about the main properties of the 50Pt50Ni catalysts such as activity, conversion and selectivity to di-branched isomers in the isomerization of n-hexane were obtained by performing catalytic tests. Concerning these properties, the catalysts supported on the synthesized zeolite Beta (Si/Al = 7.5) showed better catalytic performance compared with catalysts supported on commercial zeolite Beta (Si/Al = 9.0). Additionally to these tests, a study on the kinetics of reduction of ions Pt2+ and Ni2+ on these catalysts was conducted using X-ray absorption spectroscopy (XAS). The combination of XAS analysis and catalytic tests showed the importance of maintaining a bimetallic platinum and nickel system in order to obtain satisfactory performance of catalysts applied to the isomerization of n-hexane. The XAS results suggested that Pt2+ ions are reduced in lower temperatures compared to Ni2+ ions, and that the addition of platinum to the nickel-based samples promoted the reduction of Ni2+ ions. The catalytic results suggested that equilibrium between acid and metal sites exists during the isomerization of n-hexane. The understanding of this equilibrium is of major importance to increase the yield and selectivity to di-branched isomers.